Nosocomial pathogens associated with the mobile phones of healthcare workers in a hospital in Anyigba, Kogi state, Nigeria - E.O. Nwankwo; N. Ekwunife; K.C. Mofolorunsho (Journal of Epidemiology and Global Health, 2019)
Background: Mobile phones of healthcare workers (HCWs) could be colonized by potential bacteria pathogens. The aim of this research is to evaluate the bacterial contamination and antibiotic sensitivity pattern of isolates from mobile phones of HCWs in Grimad hospital. Method: A total of 112 swab samples were collected from the mobile phones of HCWs and students in June 2012 in Anyigba. While 56 samples were from HCWs in Grimad hospital, 56 samples were obtained from non-healthcare workers (NHCWs) who served as the control. The samples were all screened for bacterial pathogens by standard bacteriological procedures. Antibiotic susceptibility testing was done by the disc diffusion technique. Results: The rate of bacterial contamination of mobile phones of HCWs was 94.6%. Bacteria isolated from mobile phones of HCWs were more resistant to antibiotics than NHCWs phones. Staphylococcus Epidermidis (42.9%) was the most frequently isolated bacteria followed by Bacillus spp. (32.1%), Staphylococcus Aureus (25%), Pseudomonas Aeruginosa (19.6%), Escherichia Coli (14.3%), Streptococcus spp. (14.3%), Proteus spp. (12.5%), Klebsiella spp. (7.1%), and Acinetobacter spp. (5.3%). Cotrimoxazole, ampicillin and tetracycline showed high levels of resistance while gentamicin, ciprofloxacin and ceftriaxone exhibited encouraging results. Conclusion: The presence of bacteria pathogens associated with nosocomial infection was identified. Transmission of pathogens can be reduced by hand hygiene and regular cleaning of mobile phones.